Cyclosporine A – Induced gingival overgrowth and proliferating cell nuclear antigen expression in experimental periodontitis - Ricardo, Lucilene Hernandes; do Prado, Renata Falchete [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; da Silva Peralta, Felipe; Pallos, Debora (Elsevier, 2019)
The most important microscopic characteristic of Cyclosporine A-induced gingival overgrowth is fibroepithelial hyperplasia. Objective: The objective was to investigate the influence of previous exposure to Cyclosporine A over gingival epithelium in experimental periodontitis in rats. Methods: Twenty Wistar rats with 12 weeks-old were divided into four groups with 5 animals each: Control Group (CG); Cyclosporine Group (CsAG); Ligature group (LG) and Cyclosporine and Ligature Group (CsALG). Daily doses of CsA (10 mg/kg) were applied to CsAG and CsALG during 60 days since the beginning of the experiment and, a ligature was placed in LG and CsALG 30 days after the beginning of the experiment. After 60 days, animals were euthanized and gingival tissue was processed to histomorphometric analysis of epithelial thickness (mm2), immunohistochemical expression of PCNA (%) and inflammatory response. Data were analyzed by Kruskal-Wallis and Mann Whitney at 0.05 significance level. Results: Considering epithelial thickness, CG was thinner than all groups, CsALG was the largest and CsAG and LG were similar between each other. Regarding the PCNA expression CG (16.46 ± 9.26) was similar to CsAG (34.47 ± 19.75) and, LG (59.02 ± 10.33) was similar to CsALG (40.59 ± 18.25). Significant difference (p < 0.05) occurred only in inflammation presence comparing CG/LG and CsAG/CsALG. A weak positive correlation between the number of PCNA+ and inflammatory cells (p = 0.001; r = 0.611) was observed. Conclusion: Based on these results it was concluded that the enlargement of gingival epithelium observed in experimental periodontitis can be increased by previous exposition to CsA and inflammatory conditions enhanced proliferative activity of the keratinocytes.
Keywords: Cyclosporine A; Epithelial hyperplasia; Gingival overgrowth; Immunohistochemical analysis; Inflammation; PCNA; Proliferative index